Furniture design : an introduction to development, materials and manufacturing - Lawson, Stuart (London, 2013)
"Furniture Design is a comprehensive guide and resource for furniture designers. Primarily written for students, it discusses pioneering contemporary and historical designs, whilst also providing in-depth answers to designers' questions, about function, materials, manufacturing and sustainability, integrating guidance on all of these subjects in one easily accessible book."-
Keywords: Furniture design -- Architecture; accessories